Teores de metais em sedimentos e nutrientes, nas águas de uma microbacia da nascente do Rio São Lourenço, Campo Verde-MT - Oliveira, Mônica Bidarra (2012)
The present study evaluated the concentrations of metals (Fe, Cu, Mn, and Zn), in the carried (SC) and bottom sediments (SD); and in nutrients (F- , Cl- , NO2 - , NO3 - , PO4 3-, SO4 2-, and K+ ) in the runoff (AE), superficial (AS), and ground waters (AP/P) from the São Lourenço micro-watershed, near the urban area in the municipality of Campo Verde – MT. The intense use of agrochemicals (fertilizers and manure) is present in this region because its typical agricultural activity in which soy, cotton, and corn crops are grown. The sampling procedure was performed over one hydrological year from October/09 to September/10. The analyses in the waters followed the methodologies described in the STANDARD METHODS (2005) for the anions F- , Cl- , NO2 - , NO3 - , PO4 3-, and SO4 2-, and by Tedesco, et al. (1995) for the cation K+ . The preparation of samples for the determination of metals in the sediments was made by nitro-perchloric digestion and determined by flame atomic absorption spectrometry. The sediment concentrations presented in mg L-1 followed the order: Fe>Cu> Zn>Mn. The Fe levels were above the recommended values in the literature at all points. The positive correlations between the metals and CTC, fraction (silt and clay) and MO, in both environments (SC and SD) and periods of rain and drought, were evidenced. The formation of four groups, with similarities between them, was observed through the grouping analysis (Cluster) due to the characteristics of the soils. The nutrients were present in low concentrations in the collected waters when compared to the maximum allowed values (VMP) from the standards established by the environmental agencies. Elevated levels of the ions K+ , NO3 - , and Cl- were observed in AE. High levels of Cl- were registered in AS. The highest concentrations of NO3 - , Cl- , and K+ were detected in AP/P. The significant correlations between these ions strongly suggested the use of agricultural fertilizers in the region. The loss of these nutrients by the action of rain was evident in the positive correlations. The numerical comparison of the averages from AE1, AE2, AE3, and AE4 indicated a decrease in the concentration of nutrients. This decrease in concentrations of nutrients in AE can be linked to the recovery plan for the area through the planting of seedlings that began at the end of 2009. The range of vegetation contributed in reducing the amount of nutrients and carried sediments in the direction toward the dam. The continuity of farming activities, without adequate environmental management, will lead to the tendency to increased levels of metals and nutrients, thereby jeopardizing the quality of water at the source of the São Lourenço River– MT.